Harmonizing lecture slides presentations with background music: thematic analysis of students experiences - Bannor, Gyasi Alfred; Dissou Arthur, Yarhands (Frontiers in Psychology, 2025)
Research shows that background music (BM) help people stay engaged and focused while learning, reading, or performing other cognitive tasks, though it can sometimes be distracting. However, its role in learning during lecture slide presentations is not well understood. This study explores the impact of BM on learning during PowerPoint lecture presentations among a convenient sample of 23 Master of Philosophy (MPhil) students in Ghana. Using a descriptive phenomenological qualitative design, a semi-structured interview was employed to elicit students’ responses of their experiences. Thematic analysis was conducted of the interview data and three main themes were identified: (i) staying engaged, where BM made the learning environment livelier, (ii) effect on concentration, with mixed responses on whether BM helped or distracted attention, and (iii) effects on learning, where BM supported some students’ understanding, but hindered that of others. The findings suggest that BM’s impact on learning during slide presentation context is influenced by individual factors. That is, the effects of BM may differ based on individual or contextual factors. Thus, we recommend the need for lecturers to consider individual students regarding integrating BM into PowerPoint presentations.